Minocycline relieves neuropathic pain in rats with spinal cord injury via activation of autophagy and suppression of PI3K/Akt/mTOR pathway - Leyan Qiao; Qian Tang; Zhongzhe An; Jun Qi (Elsevier, 2023)
Objective: In this study, we studied whether minocycline hydrochloride improved neuropathic pain induced by spinal cord injury (SCI) in rats through PI3K/Akt pathway. Methods: The SCI was induced by compressed at level of T9-T11 of spinal cord in Sprague Dawley male rats. Animals were given different concentrations of minocycline (3 mg/kg, 30 mg/kg, 90 mg/kg) at the first and 24 h after SCI, then subsequently every 7, 12, 16, 20, 25 days via peroral route. The locomotor function was assessed by Basso Mouse Scale (BMS). The changes of spinal cord tissues were observed by HE. The inflammatory cytokines in spinal cord, IL-6, IL-1β and TNF-α, were measured by ELISA. The LC3B levels of spinal cord were observed by immunofluorescence. The autophagy related proteins and PI3K/AKT pathway related proteins were analysed by Western blot. Furthermore, the PI3K/AKT pathway inhibitor LY294002, and activator IGF-1 were used to confirm the mechanism of minocycline. Results: Contrasted to sham group, the inflammatory response in spinal cord was enhanced after SCI. Compared with the SCI rats, minocycline treatment significantly improved the locomotor activity, pathological injury of spinal cord, suppressed the levels of inflammatory factors. In addition, minocycline treatment upregulated autophagy response in damaged spinal cord through increasing LC3B, Beclin-1 and decreasing P62. The results of mechanism study showed that minocycline treatment clearly suppressed phosphorylation of PI3K, Akt and mTOR proteins expression. Conclusion: Minocycline could improve neuropathic pain induced by SCI through activating autophagy and inhibiting PI3K/AKT/mTOR pathway.